HAJJ FINANCIAL MANAGEMENT OPERATIONAL ANALYSIS AT MINISTRY OF RELIGION AFFAIRS - Vitri Sarastuti; R Luki Karunia; Enan Hasan; Asfan Shabri (Journal of Business Administration Economics & Entrepreneurship, 2022)
Financial Statements to the President and Parliaments (DPR) are regulated in Minister of Religion Regulation (PMA) Number 28 of 2019 concerning the Implementation of Hajj Financing. The case study is a research approach used, from Observation and Financial Management of Hajj Operations 1440 H/2019 M (Audited). Data Analysis using Qualitative Descriptive Method. The results of the Financial Report as accountability and transparency of the Ministry of Religion as the organizer of the Hajj. The results of budget analysis and verification, as an improvement strategy in Hajj Financial Management (HFO/PKOPIH) and the use of activities in Financial Management in Indonesian and Saudi Arabian work units, namely (a) Hajj Fund Management has BPIH Financial Report Setting Standards; (b) Accounting Standards using operational financial guidelines for the Organization of the Hajj; (c) verification as an administrative audit of financial accounting controls; (d) reconciliation activities compare the records of the parties related to the Financial Accounting for the Organization of the Hajj Pilgrims; (e) Supervision of the Verifier as control of the Realization Plan. Implications of the Ministry of Religion The government builds an Accounting System Application System, effective and efficient accounting makes accountability, real time and the Hajj fund management body makes plans, realizations and PKOPIH reports.Keywords: operational financial management of the Hajj; organizing hajj and umrah; verification; reconciliation; financial management of Hajj operations